2020
DOI: 10.1371/journal.pone.0242057
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the role of exosomal microRNA in colorectal tumorigenesis using human colorectal cancer cell lines

Abstract: Exosomes are a group of small membranous vesicles that are shed into the extracellular environment by tumoral or non-tumoral cells and contribute to cellular communication by delivering micro RNAs (miRNAs). In this study, we aimed to evaluate the role of exosomal miRNAs from colorectal cancer cell lines in tumorigenesis, by affecting cancer-associated fibroblasts (CAFs), which are vital constituents of the tumor microenvironment. To analyze the effect of exosomal miRNA on the tumor microenvironment, migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 78 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…SEUMC 2019-12-028). CAFs were isolated from the collected tumour samples o and cultured as previously described 12 .…”
Section: Wound-healing Assaymentioning
confidence: 99%
“…SEUMC 2019-12-028). CAFs were isolated from the collected tumour samples o and cultured as previously described 12 .…”
Section: Wound-healing Assaymentioning
confidence: 99%
“…Exosomal miR-25, miR-130b and miR-425 have been similarly implicated in TAM polarization and C-X-C motif chemokine 12 (CXCL12)/C-X-C motif chemokine receptor 4 (CXCR4)-dependent liver metastasis ( 182 ). On the other hand, CRC cell-derived exosomes have been found to diminish the migration of THP-1 monocytes in vitro via the delivery of let-7d, which can downregulate the chemokine C-C motif chemokine ligand 7 (CCL7) ( 183 ), suggesting that exosomal miRNAs can aid immune evasion by interfering with immune cell chemotaxis. A list of exosomal miRNAs that have been implicated in different steps of the metastatic cascade is presented in Table I .…”
Section: Crc Exosomal Mirnas Implicated In Emt and Organotropismmentioning
confidence: 99%
“…4,5 Cancer-associated fibroblasts (CAFs) are a crucial component of the TME that promote tumorigenesis by interacting with cancer cells. 6,7 CAFs act as vital modulators in communication between tumor and stroma in most solid tumors, and they interact with all other cells within the TME and promote tumor progression by secreting various chemokines and cytokines. 8,9 For example, Li et al showed that CAFs were able to increase PD-L1 level in mice cancer cells, leading to an immunosuppression microenvironment by containing CXCL5.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment (TME) refers to the surrounding area of tumor growth, which has been shown to play a key role in regulating tumor progression 4,5 . Cancer‐associated fibroblasts (CAFs) are a crucial component of the TME that promote tumorigenesis by interacting with cancer cells 6,7 . CAFs act as vital modulators in communication between tumor and stroma in most solid tumors, and they interact with all other cells within the TME and promote tumor progression by secreting various chemokines and cytokines 8,9 .…”
Section: Introductionmentioning
confidence: 99%